THE ROLE OF TEACHING FOREIGN LANGUAGES IN MEDICAL UNIVERSITY - Aitmuratova Perkhan Genzhebaevna; Esanova Maftuna Baxadirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the study of a foreign language course and the basics of medical terminology in medical institutes, universities and academies, intended, first of all, to prepare a terminologically literate doctor.